2010
DOI: 10.1007/s11460-010-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithm optimization of broadband microstrip antenna

Abstract: Genetic algorithm (GA) is utilized to design microstrip patch antenna shapes for broad bandwidth. A new project based on GA and high frequency simulation software (HFSS) is proposed to perform optimization. Reasonable agreement between simulated results and measured results of the GA-optimized design is obtained. The optimized patch design exhibits a three-fold enhancement in bandwidth when contrasted with a standard square microstrip antenna, showing the validity of this project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…D-H is a connecting rod fastened to the coordinate system construction method. Use to describe the relative position and relative movement between the adjacent link of robot [5][6].…”
Section: Methods Of D-hmentioning
confidence: 99%
“…D-H is a connecting rod fastened to the coordinate system construction method. Use to describe the relative position and relative movement between the adjacent link of robot [5][6].…”
Section: Methods Of D-hmentioning
confidence: 99%
“…This section reviews existing literature along with a discussion of future research challenges. A genetic algorithm (GA) technique is proposed to optimize the geometry of square-shaped MPA for WB and broadband applications [27][28]. Therefore, Silva et al [29] suggested a circular-ring MSA design optimization by using the selforganizing GA (SOGA) technique with UWB features.…”
Section: Related Workmentioning
confidence: 99%
“…( 28)). Now, the other coordinates of the antenna radiators (i.e., p 1 , p 2 , p 3 , p 4 , and p 5 ) are obtained as per equations (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), which are found using the GSA-QPSO algorithm. Though, MATLAB is applied as the key development tool; where HFSS has been utilized to validate the performance of reflection coefficients and radiation characteristics.…”
Section: System Implementationmentioning
confidence: 99%